2018
DOI: 10.1187/cbe.17-12-0288
|View full text |Cite
|
Sign up to set email alerts
|

A Course-Embedded Comparison of Instructor-Generated Videos of Either an Instructor Alone or an Instructor and a Student

Abstract: Instructor-generated videos have become a popular way to engage students with material before a class, yet this is a relatively unexplored area of research. There is support for the use of videos in which instructors tutor students, but few studies have been conducted within the context of a classroom. In this study, conducted in a large-enrollment college physiology course, we used a randomized crossover design to compare the impact of two types of instructor-generated videos that students watched as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
0
16
3
Order By: Relevance
“…A summary of which students were more likely to find asking and answering questions helpful and which students reported answering and asking questions most frequently are reported in Fig 5 . Despite literature suggesting that students may be confused by other students’ questions and answers [ 26 ] or exasperated by peers who contribute too much to whole-class discussion [ 5 ], we found that students overwhelmingly reported that other students asking and answering questions was helpful to them. Notably, compared to continuing generation college students, first-generation college students were more likely to report that they found other students asking questions in large-enrollment college science courses to be helpful.…”
Section: Discussioncontrasting
confidence: 92%
“…A summary of which students were more likely to find asking and answering questions helpful and which students reported answering and asking questions most frequently are reported in Fig 5 . Despite literature suggesting that students may be confused by other students’ questions and answers [ 26 ] or exasperated by peers who contribute too much to whole-class discussion [ 5 ], we found that students overwhelmingly reported that other students asking and answering questions was helpful to them. Notably, compared to continuing generation college students, first-generation college students were more likely to report that they found other students asking questions in large-enrollment college science courses to be helpful.…”
Section: Discussioncontrasting
confidence: 92%
“…Felicia and Antoinette’s shared opinion that it can be beneficial to hear science described by their classmates in different terms than the instructor uses is supported by previous research that shows that students recognize the benefit of learning science from other students who think more like novices and less like the expert instructor (Chi et al 2004; Cooper et al 2018b; Harper and Daane 1998). Further, studies have shown that peer instruction, or asking students to explain concepts to each other during class, improves student performance on formative assessments such as clicker questions (Crouch and Mazur 2001; Smith et al 2009).…”
Section: Resultsmentioning
confidence: 86%
“…One such factor is whether a video is scripted or naturally occurring, such as a conversation between a tutor and their student in an office hour. Work by Cox et al (1999) and Cooper et al (2018) found null results in learning between unscripted monologue and dialogue videos. Cox et al (1999) speculated that the dialogue condition required participants to expend more cognitive resources than the monologue in order to parse both instructor and student's contributions.…”
Section: Vicarious Learning Monologue Vs Dialoguementioning
confidence: 98%
“…As a mediator, however, the dialogue may have held participants' interest more effectively than the monologue, and thus learning was not negatively impacted. Cooper et al (2018) added to these speculations, finding that a majority of participants, when presented with unscripted monologue and dialogue videos, reported a preference for monologue videos -common reasons given for this preference included the directness of monologue presentation, which contrasted the perceived confusing, disorganized, and misleading nature of the dialogue format. By comparison, participants who preferred the dialogue format focused only on the perceived advantages of the format, such as the inclusion of a student's perspective, the relatability of the tutee, and the tutoring environment of the dialogue (Cooper et al, 2018).…”
Section: Vicarious Learning Monologue Vs Dialoguementioning
confidence: 99%
See 1 more Smart Citation